Genetic and molecular analysis of recessive alleles at the pink-eyed dilution (p) locus of the mouse. - Lyon, M F (1992)
Recessive mutant alleles at the pink-eyed dilution (p) locus on mouse chromosome 7 reduce pigmentation of both the coat and eyes. Here we describe the properties and complementation interactions of 10 p alleles, including 6 not previously reported. Several alleles that cause additional phenotypes affecting development, reproduction, and behavior were shown to be deletions by using DNA probes derived from the p region. An alignment of functional and marker-defined units is proposed, giving a linear complementation map that orders at least four functional loci. The characterization of a nested set of deletions around p will facilitate detailed molecular analyses of the genes and developmental functions associated with this part of the mouse genome.